Movement-related and steady-state electromyographic activity of human elbow flexors in slow transition movements between two equilibrium states - Tal'nov, A.N; Cherkassky, V.L; Kostyukov, A.I (Neuroscience, 1997)
The electromyograms were recorded in healthy human subjects by surface electrodes from the mm. biceps brachii (caput longum et. brevis), brachioradialis, and triceps brachii (caput longum) during slow transition movements in elbow joint against a weak extending torque. The test movements (flexion transitions between two steady-states) were fulfilled under visual control through combining on a monitor screen a signal from a joint angle sensor with a corresponding command generated by a computer. Movement velocities ranged between 5 and 80°/s, subjects were asked to move forearm without activation of elbow extensors. Surface electromyograms were full-wave rectified, filtered and averaged within sets of 10 identical tests. Amplitudes of dynamic and steady-state components of the electromyograms were determined in dependence on a final value of joint angle, slow and fast movements were compared. An exponential-like increase of dynamic component was observed in electromyograms recorded from m. biceps brachii, the component had been increased with movement velocity and with load increment. In many experiments a statistically significant decrease of static component could be noticed within middle range of joint angles (40–60°) followed by a well expressed increment for larger movements. This pattern of the static component in electromyograms could vary in different experiments even in the same subjects. A steady discharge in m. brachioradialis at ramp phase has usually been recorded only under a notable load. Variable and quite often unpredictable character of the static components of the electromyograms recorded from elbow flexors in the transition movements makes it difficult to use the equilibrium point hypothesis to describe the central processes of movement. It has been assumed that during active muscle shortening the dynamic components in arriving efferent activity should play a predominant role. A simple scheme could be proposed for transition to a steady-state after shortening. Decrease of the efferent inflow can evoke internal lengthening of the contractile elements in muscle and, as a result, hysteresis increase in the muscle contraction efficiency. Effectiveness in maintenance of the steady position seems to also be enhanced due to muscle thixotropy and friction processes in the joint. Hysteresis after-effects in elbow flexors were demonstrated as a difference in steady-state levels of electromyograms with oppositely directed approaches to the same joint position.